Newly designed resorcinolate binding for Ru(II)- and Re(I)- polypyridyl complexes on oleic acid capped tio2 in non-aqueous solvent: prolonged charge separation and substantial thermalized 3MLCT injection - Banerjee, Tanmay; Kaniyankandy, Sreejith; Das, Amitava; Ghosh, Hirendra Nath (Journal of Physical Chemistry C, 2013)
Femtosecond pump–probe spectroscopic studies on a series of newly synthesized resorcinol-based Ru(II) and Re(I) complexes on oleic acid capped TiO2 nanoparticles have been carried out in chloroform, and the results are compared with those of the catechol analogues. The ruthenium complex shows biexponential injection; the second component arises due to injection from the thermally equilibrated 3MLCT states as a result of a weaker strength of the resorcinolate binding. Also, in comparison with catechol binding, as a result of a greater diffusion of the injected electrons into TiO2, the back electron transfer (BET) is slowed down significantly for the ruthenium complex. These are distinctive observations for any mononuclear ruthenium–polypyridyl–enediol complex reported thus far. However, the rhenium complex educes single exponential ultrafast injection (<120 fs) because of apparent injection in a high density of states and shows the most prominent results with ∼50% slowdown in the charge recombination rate as compared to the analogous catechol bound system. These results exemplify the probable development of highly capable sensitizer dyes with resorcinol as the anchoring group for the development of efficient dye-sensitized solar cells.